Penetapan Kadar Flavonoid Total Sari Rimpang Temu Mangga (Curcuma mangga Valeton & Zijp) Segar dan Terfermentasi - Ghina Hanifah Nur Azizah; Siti Hazar; Fetri Lestari (UNISBA Press, 2024)
Abstract. The rhizome of temu mango (Curcuma mango Valeton & Zijp), is a plant from the zingiberaceae family that has a variety of secondary metabolites that are responsible for various pharmacological activities including antioxidants, antipyretics, and antitoxins. One of the secondary metabolites found in the rhizome of the temu mango is the group of flavonoid compounds which are included in phenolic compounds. Efforts that can be made to increase the levels of this group of compounds are through the fermentation process. Fermentation is a method of bioprocessing processed food that is reported to increase the bio-conversion of phenolic compounds from conjugated form to their free form, so that it is expected to increase their bioactivity in the body. This study was conducted to see the effect of fermentation on the total flavonoid content of fresh and fermented temu mango rhizomes, where fermentation was carried out using Lactobacillus bulgaricus starter with a fermentation period of 18 and 24 hours. The determination of the total flavonoid content of the test sample was carried out using the AlCl3 reagent with quercetin as the standard compound and then measured using UV-Vis spectrophotometry. Based on the results of the study, through the fermentation process, there has been an increase in the total flavonoid content of fermented temu mango rhizome juice for 18 and 24 hours compared to the fresh juice with a p < value of 0.05. The total flavonoid content of fresh, fermented mango rhizome juice for 18 hours and 24 hours, respectively, were 66,364±4,212; 80,685±5,155; and 92,846±2,953 mgQE/100 grams of Fresh Rhizomes. Abstrak. Rimpang temu mangga (Curcuma mangga Valeton & Zijp), merupakan tanaman dari famili zingiberaceae yang memiliki beragam metabolit sekunder yang bertanggung jawab atas berbagai macam aktivitas farmakologi diantaranya sebagai antioksidan, antipiretik, dan antitoksin. Salah satu metabolit sekunder yang terdapat pada rimpang temu mangga yaitu golongan senyawa flavonoid yang termasuk kedalam senyawa fenolik. Upaya yang dapat dilakukan untuk meningkatkan kadar golongan senyawa ini adalah melalui proses fermentasi. Fermentasi merupakan metode bioproses olahan pangan yang dilaporkan dapat meningkatkan bio-konversi senyawa fenolik dari bentuk terkonjugasi ke bentuk bebasnya, sehingga dengan demikian diharapkan dapat meningkatkan bioaktivitasnya didalam tubuh. Penelitian ini dilakukan untuk melihat pengaruh fermentasi terhadap kadar flavonoid total sari rimpang temu mangga segar dan terfermentasi, dimana fermentasi dilakukan menggunakan starter Lactobacillus bulgaricus dengan lama fermentasi selama 18 dan 24 jam. Penetapan kadar flavonoid total sampel uji dilakukan dengan menggunakan reagen AlCl3 dengan kuersetin sebagai senyawa standarnya lalu diukur menggunakan spektrofotometri UV-Vis. Berdasarkan hasil penelitian, melalui proses fermentasi telah terjadi peningkatan kadar flavonoid total sari rimpang temu mangga terfermentasi 18 dan 24 jam dibandingkan dengan sari segarnya dengan nilai p < 0.05. Kadar flavonoid total sari rimpang temu mangga segar, difermentasi 18 jam, dan 24 jam, berturut-turut adalah 66,364±4,212; 80,685±5,155; dan 92,846±2,953 mgQE/100 gram Rimpang Segar.